Representasi Visual sebagai Aspek Kemampuan Pedagogik Guru dalam Pembelajaran Komunikasi Bahasa Arab - Azisi; Nurfaiza; Dwi Juli Priyono; Badri (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
This study aims to explore the role of visual representation in the teaching of maharah kalam, especially in the context of understanding complex Arabic concepts and improving students' speaking skills. The focus is on evaluating effective teaching strategies that integrate visual representation in the maharah kalam learning process as well as their impact on students' comprehension and speaking skills. The method used in this study is qualitative method, with data collection techniques in the form of literature studies and documentation. The results showed that visual representations such as diagrams and charts were effective in improving students' understanding of Arabic as well as improving their speaking skills. The role of teachers in utilizing visual representation is very important to create an interactive learning environment. The use of visual media can help facilitate better understanding and encourage active involvement of students in the learning process. Overall, visual representation becomes an integral part of teaching practice to improve Arabic communication skills, and it is important for teachers to utilize it in creating a dynamic and interactive learning environment.